2016
DOI: 10.1177/1545968315619697
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in the Acute Phase of Severe Traumatic Brain Injury

Abstract: Background and Objectives The onset of pervasive sleep-wake disturbances associated with traumatic brain injury (TBI) is poorly understood. This study aimed to (a) determine the feasibility of using polysomnography in patients in the acute, hospitalized stage of severe TBI and (b) explore sleep quality and sleep architecture during this stage of recovery, compared to patients with other traumatic injuries. Methods A cross-sectional case-control design was used. We examined the sleep of 7 patients with severe T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 30 publications
2
48
1
Order By: Relevance
“…The sleep characteristics in the present sample are consistent with those of others samples following TBI in post-hospital phases. 5,15,39,40 Specifically, the average sleep efficiency of the participants in this sample was 73%, lower than the 80-90% sleep efficiency recognized as normal in adults without TBI. 37,38 Despite evidence that poor sleep is a common symptom of TBI 5 and that poor sleep can undermine rehabilitative efforts 3,39 none of the nighttime rest/activity measures associate with functional outcome in a comprehensive model.…”
Section: Nighttime Rest/activity For Patients Hospitalized With Tbicontrasting
confidence: 54%
See 1 more Smart Citation
“…The sleep characteristics in the present sample are consistent with those of others samples following TBI in post-hospital phases. 5,15,39,40 Specifically, the average sleep efficiency of the participants in this sample was 73%, lower than the 80-90% sleep efficiency recognized as normal in adults without TBI. 37,38 Despite evidence that poor sleep is a common symptom of TBI 5 and that poor sleep can undermine rehabilitative efforts 3,39 none of the nighttime rest/activity measures associate with functional outcome in a comprehensive model.…”
Section: Nighttime Rest/activity For Patients Hospitalized With Tbicontrasting
confidence: 54%
“…So what? We know some studies have shown that sleep disturbances (poor sleep consolidation and architecture) are common in hospitalized patients with TBI, 12,13,14,15 but they have either all occurred in the ICU, have used only subjective measures of sleep, or have included patients with only mild TBI. Therein lies a missed opportunity for exploring nighttime sleep for patients with TBI hospitalized on the neuroscience step-down unit.…”
Section: Introductionmentioning
confidence: 99%
“…48 Studies indicate that 30-70% of TBI survivors across the entire injury spectrum experience disordered sleep after injury, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] a finding unique to traumatic cerebral injury, as traumatic spinal cord injuries do not cause similar sleep-wake disturbances. 49 Numerous studies have demonstrated that the severity of the inciting head injury does not predict the degree of sleep-wake disturbances; 6 individuals with traumatic brain insults of all severities are at risk. Reported rates vary widely due to methodological variances in many studies, including sample bias (i.e., samples referred to sleep laboratories), varied assessment methods (i.e., subjective self-report versus objective polysomnography or actigraphy), and poor recognition or underreporting by patients and clinicians.…”
Section: Epidemiologymentioning
confidence: 99%
“…For these patients, continuous intravenous sedation and analgesia were discontinued for a minimum of 48 h prior to study. Specifically, Wiseman-Hakes et al [68] found that compared to OSCI, severe TBI patients showed significantly longer duration of nocturnal sleep and earlier nighttime onset. However, as with previous studies, these authors note and caution that PSG may not be usable for portions of this population due to the confusion and agitation.…”
Section: Acute Phase (0-3 Months)mentioning
confidence: 99%